positioning a unicycle mobile robot by 2D visual servoing - KACEMI Abdelbadiaa; ABDESSELAM Sofiane; Feknous, Safia (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2020)
The task that we had to achieve by simulation in this project is the positioning relative to a landmark placed in the environment, of a unicycle mobile robot equipped with an on-board camera. The control of the robot's actuators so that it reaches the desired position is achieved with a 2D visual servo-control. The simulation was made with the CppeliaSim simulator which offers very interesting features such as the possibility of creating a three-dimensional virtual environment of our choice, using ready to use CoppeliaSim models of mobile robot and camera. In such a control system, the only sensor information comes from the camera. To determine the visual information required in the control scheme, and because of the characteristic shape of the landmark (four circles), a processing of the images captured with the camera is performed with the Hough Circle Transform using OpenCV library. The entire control program was written in C ++.
OPTION : AUTOMATION